PREFERENSI PETANI DALAM MENGHADAPI RISIKO PRODUKSI CABAI MERAH KERITING DI KABUPATEN CIANJUR - Wibisonya, Irawan; Fariyanti, Anna; Jahroh, Siti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
One indication of the risk is fluctuations in production yield. Chili as a superior competitor is the most vulnerable to fluctuations in production. The purpose of this study was to analyze the factors that influence the risk of production and farmers' policies on the risk of production. This research used purposive sampling with 66 farmers sampel size. This research used Just and Pop models which were analyzed using regression analysis and analysis of farmer relationships with utility function models. The results reflected that land area, seeds, fertilizers, pesticides and labor can increase the yield of chili. While the area of land, seeds, fertilizers, labor and planting seasons can increase the risk of chili production. Most farmers have risk takers compared to the potential for chili production.